Sistem Informasi Geografis Cagar Budaya Kota Cimahi - Asep Ririh Riswaya; Dheni Apriantsani Budiman; Eka P. Sakti; Anjas Tryana (Ma'soem University, 2022)
Cimahi city is known for its rich historical places and buildings, there are 25 historical buildings in Cimahi City that passed the verification of the Ministry of Education and Culture. It is unfortunate if the information regarding the location of the distribution of the cultural heritage has not been widely disseminated to the public, the purpose of this research is to help the community in adding insight about historical places and buildings in Cimahi City by building applications as a supporting tool. Application method is Djikstra and application creation using android Studio. With software development model SDLC and the stages of development consist of: Systems Planning, analysis, design, development, testing and Maintenance. From the results of manufacture geographic information system cultural heritage as a media to increase insight for the community. Researchers can find out cultural heritage buildings in Cimahi City, There is also a route map that can provide information for the public in accessing cultural heritage buildings in Cimahi City.